QRIS AS SUPPORTERS AND DRIVERS ECONOMIC GROWTH IN PROCESSING TRANSACTION RETAIL IN THE DIGITAL ERA - Natalios Peter Sipasulta; Dionysia Kowanda; Siti Nurafiah (Asosiasi Dosen Muda Indonesia, 2026)
The development of digital payments in Indonesia has shown significant acceleration since the launch of the Quick Response Code Indonesian Standard ( QRIS ). This paper analyzes QRIS's role in facilitating retail transaction efficiency, increasing financial inclusion for MSMEs, and its contribution to digital economic growth. Using a mixed-methods approach (analysis of secondary transactions and merchant data from Bank Indonesia, along with a review of empirical literature and MSME case studies), the paper finds that QRIS adoption correlates with increased digital retail transaction volume, expanded MSME market access, and transaction cost efficiency—factors that collectively support domestic digital economic growth. Policy recommendations focus on strengthening digital infrastructure, enhancing MSME digital literacy, and incentivizing cross-border interoperability. (Bank Indonesia)